The Manipulation effectivity of cell co-cultures in 5% CO2 incubation system to increase in vitro cattle embryo production - Syaiful, Ferry Lismanto; BP, Zesfin; Saladin, R; ., Jaswandi; ., Hendri (Indonesian Journal of Animal and Veterinary Sciences, 2010)
The purpose of this research is to determine the effectivity of various cell co-cultures of cattle embryo production by in vitro CO2 5% incubation system and get the best cell co-culture. Cell co-culture which are used in the synthesis is the oviduct cells, isthmus cells, ampulla cells, follicle cells and without cells. Data were analyzed based on completely randomized desiggn. The average growth rate/ cleavage in various cell culture was: the oviduct cell 59.24%, ampulla cell  58.69%, isthmus cell 58.25%, follicle cell 52.24% and without cells 47.76%. The average  growth of 8-16 cells embryos to various cell co-culture was: the oviduct cell 46.02%, ampulla cell 45.45%, isthmus cell 45.15%, follicle cell 43.07%, and without cell 38.50%. The mean percentage of morula in various cell co-culture treatment was: the oviduct cell 20.59%, ampulla cell 20.48%, isthmus cell 20.30%, follicle cell 16.96% and without cell 12.58%. The average percentage of embryonic growth (cleavage, 8-16 cells and morula) was not significantly different (P > 0.05).  The treatment of a variety of cell co-culture increased significantly (P>0.05), blastocysts production, namely: the oviduct cell 3.28%, ampulla cell 3.22%, isthmus cell 3.08%, follicle cell 2.45% and without cell 1.97%.  In conclusion, the treatment of various cell co-culture in 5%CO2   incubation system can increace the growth of cattle embryos in vitro.   Key words: Cell Co-Culture, In Vitro Embryo, 5%CO2 Incubation System, Cattle